Essays on American Indian and Mormon History - Rensink, Brenden W.; Hafen, P. Jane, 1955- (Book collections on Project MUSE., 2019)
"Addresses the Indian-Mormon relationship, placing the Indigenous perspective at center."--Provided by publisher